Bone Strength Estimated by Micro‐Finite Element Analysis (µFEA) Is Heritable and Shares Genetic Predisposition With Areal BMD: The Framingham Study. (19th July 2017) - Karasik, David; Demissie, Serkalem; Lu, Darlene; Broe, Kerry E; Boyd, Steven K; Liu, Ching‐Ti; Hsu, Yi‐Hsiang; Bouxsein, Mary L; Kiel, Douglas P
ABSTRACT: Genetic factors contribute to the risk of bone fractures, partly because of effects on bone strength. High‐resolution peripheral quantitative computed tomography (HR‐pQCT) estimates bone strength using micro‐finite element analysis (µFEA). The goal of this study was to investigate if the bone failure load estimated by HR‐pQCT‐based µFEA is heritable and to what extent it shares genetic regulation with areal bone mineral density (aBMD). Bone microarchitecture was measured by HR‐pQCT at the ultradistal tibia and ultradistal radius in adults from the Framingham Heart Study ( n  = 1087, mean age 72 years; 57% women). Radial and tibial failure load in compression were estimated by µFEA. Femoral neck (FN) and ultradistal forearm (UD) aBMD were measured by dual‐energy X‐ray absorptiometry (DXA). Heritability ( h 2 ) of failure load and aBMD and genetic correlations between them was estimated adjusting for covariates (age and sex). Failure load values at the non‐weight‐bearing ultradistal radius and at the weight‐bearing ultradistal tibia were highly correlated ( r  = 0.906; p  < 0.001). Estimates of h 2 adjusted for covariates were 0.522 for the radius and 0.497 for the tibia. Additional adjustment for height did not impact on the h 2 results, but adjustment for aBMD at the UD and FN somewhat decreased h 2 point estimates: 0.222 and 0.380 for radius and tibia, respectively. In bivariate analysis, there was a high phenotypic and genetic correlation between covariate‐adjusted failure load at the radius and UD aBMD (ρP  = 0.826, ρG  = 0.954, respectively), whereas environmental correlations were lower (ρE  = 0.696), all highly significant ( p  < 0.001). Similar correlations were observed between tibial failure load and femoral neck aBMD (ρP  = 0.577, ρG  = 0.703, both p  < 0.001; ρE  = 0.432, p  < 0.05). These data from adult members of families from a population‐based cohort suggest that bone strength of distal extremities estimated by micro‐finite element analysis is heritable and shares some genetic composition with areal BMD, regardless of the skeletal site. © 2017 American Society for Bone and Mineral Research.